2009
DOI: 10.3917/lang.173.0015
|View full text |Cite
|
Sign up to set email alerts
|

Comparaison du sens spatial des prépositions à travers en français et kroz en serbe

Abstract: Comparaison du sens spatial des prépositions à travers en français et kroz en serbe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(4 reference statements)
0
4
0
3
Order By: Relevance
“…As shown in M. Aurnague (2000) and D. Stosic (2002Stosic ( , 2007Stosic ( , 2009, the preposition à travers localizes a target within the landmark introduced by its nominal object and implies that the trajectory of a mobile target is extended enough with respect to the whole landmark ("constraint of minimal extension/coverage"). Utterances which combine a verb of change of posture and an à travers-headed PP are usually rejected (3-4).…”
Section: Change Of Placementmentioning
confidence: 97%
“…As shown in M. Aurnague (2000) and D. Stosic (2002Stosic ( , 2007Stosic ( , 2009, the preposition à travers localizes a target within the landmark introduced by its nominal object and implies that the trajectory of a mobile target is extended enough with respect to the whole landmark ("constraint of minimal extension/coverage"). Utterances which combine a verb of change of posture and an à travers-headed PP are usually rejected (3-4).…”
Section: Change Of Placementmentioning
confidence: 97%
“…Les relations sémantiques issues de ce type d'emploi sont multiples et on ne pourra les nommer toutes. Elles incluent par exemple la comparaison (c), la maîtrise (d), la cause (e, f), les relations logiques (g), interpersonnelles (h), thématiques (i), de concession (j), de point de vue (k), ou encore de possession (l) ou de guidage (m) (Stosic 2009) (Hoelbeek 2017).…”
Section: Au-dessous De La Feuilleunclassified
“…(cf. Aurnague and Stosic (2002) and Stosic (2002Stosic ( , 2007Stosic ( , 2009b have shown that the preposition à travers 'through' implies that the movement of the Figure is extended with respect to the whole Ground ("constraint of minimal extension/coverage").…”
Section: Classification Of French Motion Verbs: Aurnague's (2011) Criteriamentioning
confidence: 99%